Partner status moderates the relationships between sexual problems and self-efficacy for managing sexual problems and psychosocial quality-of-life for postmenopausal breast cancer survivors taking adjuvant endocrine therapy. Issue 8 (August 2019) - Dorfman, Caroline S.; Arthur, Sarah S.; Kimmick, Gretchen G.; Westbrook, Kelly W.; Marcom, Paul Kelly; Corbett, Cheyenne; Edmond, Sara N.; Shelby, Rebecca A.
Abstract: Objective: Past studies indicate that >90% of breast cancer survivors taking adjuvant endocrine therapy (AET) experience menopausal symptoms including sexual problems (eg, vaginal dryness, dyspareunia); however, research examining the impact of these problems on quality-of-life is limited. This cross-sectional study examined (1) the impact of sexual problems and self-efficacy for coping with sexual problems (sexual self-efficacy) on quality-of-life (ie, psychosocial quality-of-life and sexual satisfaction), and (2) partner status as a moderator of these relationships. Methods: Postmenopausal breast cancer survivors taking AET completed measures of sexual problems (Menopause-Specific Quality-of-Life [MENQOL] sexual subscale], sexual self-efficacy, psychosocial quality-of-life (MENQOL psychosocial subscale), and sexual satisfaction (Functional Assessment of Cancer Therapy-General item). Results: Bivariate analyses showed that women reporting greater sexual problems and lower sexual self-efficacy had poorer quality-of-life and less sexual satisfaction (all P -values < 0.05). Partner status moderated the relationship between sexual problems and psychosocial quality-of-life ( P = 0.02); at high levels of sexual problems, unpartnered women experienced poorer psychosocial quality-of-life than partnered women. Partner status also moderated the relationship between self-efficacy and psychosocial quality-of-life ( P = 0.01). Self-efficacy was unrelated to psychosocial quality-of-life for partnered women; for unpartnered women, low self-efficacy was associated with poorer quality-of-life. Partner status did not moderate the relationships between sexual problems or self-efficacy with sexual satisfaction. Conclusions: Greater sexual problems and lower sexual self-efficacy were associated with poorer psychosocial quality-of-life and sexual satisfaction among postmenopausal breast cancer survivors taking AET. Interventions to address sexual problems and sexual self-efficacy, particularly among unpartnered women, may be beneficial for improving the well-being of postmenopausal breast cancer survivors on AET.